(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The aim of this study was to characterize in detail the exceptionally preserved eolian morphology within the uppermost section of the Lower Cretaceous Troncoso Inferior Member at the classic outcrop locality of Loma La Torre in northern Neuquén, Argentina. The major motivations for this work are to provide new perspectives on the current knowledge of the system at this locality and to analyze the implications of a detailed study for the adequate construction of subsurface models. The Troncoso Inferior Member is one of the most important conventional hydrocarbon reservoirs in the Neuquén Basin. In the northern Neuquén province, its upper section is characterized by the preservation of an eolian dune field, with the best reservoir properties, overlain by marine evaporites. The elaboration of a detailed stratigraphic framework was successful in identifying multiple independent eolian sequences and allowed the isolation of the last eolian event, responsible for the preserved morphology. A combination of several surveying methods, including total station and 3D photogrammetrybased models, were used for a precise mapping of stratigraphic surfaces across a 7.5-km-long section. The resulting dataset was analyzed within RMS© software, which provided multiple realizations of depth and thickness maps. Results revealed a system of dunes and draa of linear type and a WSW-ENE orientation, associated with small-scale features both superimposed to the main bedforms and in the interdune areas. Measurements of morphological parameters of the major bedforms, including spacing, width and height, along with interdune width, were performed. Comparison with a modern-day analog of similar scale and characteristics provided valuable insights on the environmental conditions which constrained this system and the singularities of its construction, accumulation and preservation. Our results suggest that these dunes underwent construction under dry conditions and a limited supply or availability of sand, most likely under a bimodal wind regime, and that their preservation is entirely related to subsequent marine transgression. Moreover, this study highlights that modeling this unit in the subsurface with the detail required for managing mature fields requires a very good understanding of the system evolution.